Hereditary Spherocytosis : A Clinical Experience - F. X. Santoso; Sukardi Sukardi; Bambang Permono; Netty R. H. T.; S. Untario (Paediatrica Indonesiana, 1988)
Although hereditary spherocytosis is a common cause of hemolytic anemia among whites of Northern European descent, it is uncommon in Asia. In the past 8.5 years (from December 1978 to June 1987), we found only six cases of hereditary spherocytosis. They were 3 males and 3 females, and their ages ranged from 3 months to 8 years, with a mean age of 3.3 years. The most common presenting complaint was anemia (6 cases) followed by jaundice (4 cases) and splenomegaly (4 cases). Other symptoms were fever, abdominal pain and hepatomegaly. The mean hemoglobin concentration of these patients was 7.5 g/dl, in which 2 patients had severe anemia (less than 6 g/dl). Reticulocyte count ranged from 1.9% to 10% (mean 5.9%). All patients were found to have spherocytosis in their peripheral blood smears and an increased red blood cell fragility. Splenectomy was performed in one patient. There was no significant complication after operation in a 7-month follow up. The clinical manifestation returned to normal and the mean hemoglobin concentration increased. The existence of hereditary spherocytosis could not be proven in almost all parents of the patients. Based on this fact, is 'congenital spherocytosis' a more suitable term instead of hereditary spherocytosis?